When the Tree Falls and No One Hears It: On Being Dropped and Learning to Hold. (2nd January 2016) - Hidary, Simone
ABSTRACT: This case study focuses on a student therapist's reflections upon a premature termination that occurred in her work with an adolescent male patient. The therapeutic process is traced back to the beginning of treatment, and the article delineates the extent in which the patient's early interpersonal experiences influenced the development of the therapeutic alliance. The author addresses several themes that evolved throughout the treatment, including the patient's experience of unpredictability and instability and his inconsistent understanding of time, and the ways in which these experiences ultimately influenced the treatment's ending. The article describes the therapist's development as a clinician over the course of the treatment, focusing on the various experiences that helped her consolidate a dynamic understanding of the holding environment.